Identification and Functional Characterization of Upregulated Hub Genes in Adenocarcinoma across Multiple Organ Sites - Romero, Ricardo; Bastida, Dulce M. A. (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This study aimed to identify and characterize key hub genes involved in adenocarcinoma progression across multiple organ types via integrative bioinformatics analysis. Methods: Gene expression datasets from GEO and GEPIA2 were analyzed to identify genes whose expression was upregulated across various adenocarcinoma types. Protein‒protein interaction networks were constructed, and hub genes were identified. Transcription factors and microRNA regulatory networks were mapped, and functional enrichment analysis was performed. Results: Ten hub genes (CHEK1, CDC20, ANLN, RRM2, CCNB1, CCNA2, KIF23, TOP2A, BUB1, and KIF11) were consistently overexpressed in six adenocarcinoma types and linked to cell cycle regulation and mitotic progression. In prostate adenocarcinoma, five of these genes were not significantly overexpressed. Survival analysis revealed that most hub genes were associated with poorer survival. Regulatory network analysis identified key transcription factors (e.g., TP53 and MYC) and miRNAs (e.g., hsa-miR-103a-3p and hsa-let-7e-5p) as modulators of these genes. Conclusions: This integrative approach identified critical hub genes and regulatory networks involved in adenocarcinoma progression, offering potential avenues for targeted therapies and emphasizing the importance of personalized strategies for different adenocarcinoma subtypes.